Republic of Serbia : First Review under the Policy Coordination Instrument-Press Release; and Staff Report. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2018)
Recent economic developments. The program is broadly on track and the economy is growing strongly, supported by private consumption, investment, and exports. Fiscal performance remains sound, modernization of the tax administration has accelerated, and public debt has fallen sharply. Inflation remains below the mid-point of the NBS inflation band, while the NBS has kept rates on hold since April. Both credit and private sector wage growth are strengthening. Program performance. Quantitative targets (QTs) for end-September 2018 were met, apart from a minor deviation on the QT for domestic arrears. Most reform targets (RTs) have been implemented, albeit some with delays. Staff recommends completion of the first review under the Policy Coordination Instrument and modification of QTs for end-March and an establishment of end-September 2019 QTs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet